Using IT Project Management Methodologies to Implement an Intranet Network at the Higher Institute of Engineering Technologies in Zliten (Comprehensive Journal of Science, 2025)
This research paper aims to examine the application of Information Technology Project Management tools and methodologies in the implementation of an intranet network project at the Higher Institute of Engineering Technologies in Zliten. The study discusses all phases of the project life cycle, beginning with the initiation and planning phase, moving through the implementation and performance monitoring stages, and concluding with the project closure phase. The paper places particular emphasis on the unique challenges encountered within an educational and technical institutional environment and proposes practical solutions tailored to these circumstances.The significance of this study stems from the crucial role that intranet networks play in improving internal communication, enhancing administrative performance, and supporting academic and educational processes. The research highlights the necessity of adopting structured project management methodologies to ensure the successful execution of the intranet system in a manner that meets the institution’s needs while adhering to the principles of efficiency, quality, and resource optimization.The study also examines the importance of effective planning and accurate resource allocation, alongside risk management strategies that mitigate potential obstacles, whether technical, administrative, financial, or environmental. Additionally, the research sheds light on the role of continuous performance monitoring and evaluation mechanisms in enhancing decision-making, ensuring transparency, and maintaining alignment between project outcomes and predefined objectives.Moreover, the paper discusses the potential added value of implementing the intranet project, such as creating a unified digital platform that enables information sharing, facilitates workflow, supports electronic archiving, and improves communication among administrative staff, faculty members, and students. The research concludes that adopting IT project management methodologies contributes significantly to the success and sustainability of technological infrastructure projects in educational institutions, and it recommends conducting further studies focusing on digital transformation and smart campus initiatives to maximize institutional benefit.
Keywords: Intranet network; Project Life Cycle; Agile; Gantt Chats; End Users; SCRUM; PRINCE2